Current approaches addressing oral health practitioners' responsiveness to child abuse and neglect: A scoping review protocol. - Heuiwon Han; Jane Koziol-McLain; Zac Morse; Amanda B Lees (PLoS ONE)
Introduction Child abuse and neglect (CAN) poses significant risks, causing severe and long-lasting effects on a child's well-being, including physical and mental health and learning and socializing capabilities. Oral health practitioners (OHPs) uniquely position themselves to identify signs of maltreatment in the orofacial area, offer appropriate support, and collaborate with a multidisciplinary team. The literature has shown that OHPs under-report child protection concerns to a statutory child protection agency. Responding to CAN is often hindered by various factors, such as the fear of making false accusations and insufficient knowledge to detect and report potential cases. However, the literature lacks a comprehensive understanding of the strategies and interventions that can address the responsiveness of OHPs and other professionals to child protection issues. This scoping review aims to provide a broad overview and map the literature on the existing approaches to enhance the responsiveness of OHPs in child protection. Materials and methods The proposed scoping review will be conducted following the JBI methodology for scoping reviews guideline and reported using the PRISMA-ScR guideline. The first exploratory search is conducted to refine the search strategy and inclusion and exclusion criteria. The second search will include MEDLINE (EBSCO), CINAHL (EBSCO), Dentistry & Oral Science Source (EBSCO), Cochrane Library, and Scopus, with a date range from January 2000 to March 2023. The third search will involve reference list searching and gray literature searching in Google and Google Scholar. Government and international health organizations' websites will be searched for policies and guidelines. The review will consider studies that report the current approaches to address OHPs' responsiveness to CAN in any setting. Two reviewers will independently select sources and extract data. Any disagreements will be resolved by consensus of the research team. The extracted data will be presented in a tabulated chart with a narrative summary.